Pelestarian Bahasa Jawa Halus (Krama Inggil) pada Anak sebagai Bentuk Pemberdayaan Bahasa Lokal dan Upaya Penguatan Jati Diri Bangsa di Desa Kedungbanjar Sambeng Lamongan - Janeko Janeko; M. Ainun Na’im; Elita Lailatul Marzuqoh; Eka Lu’lu’atul Fitriyah; Rizky Ayu Nigtiaz (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Every place or region must have a pent-up potential that if harnessed would have a tremendous impact on a place or region. Such potential can be used to develop and improve from a place or region, as can a village flooded with colddings. Today, the Javanese language in particular is falling significantly because of external influences and globalization that gradually push out Java. The Javanese language and its presence are so important, the Javanese language itself is an indigenous language that is an Indonesian national culture still spoken in everyday life. The Javanese language itself has its own level of language use, such as ngoko, alus manners and ingratatedness. The use of vulgar language over time has been sparse even though such crude manners are very important asa courtesy and respect for an older person. In reality, most communities in general are mostly children who are drowning in weak Javanese. This assistance uses the PAR (Partysipatory Action Research) method, which is a research methodology that invites individuals and communities to participate actively by participating in activities in the same construction or facility with the knowledge they have. In its implementation there are several stages, namely analyzing problems, preparing program planning, program implementation and program evaluation. Efforts to develop and maintain the Javanese language can be done through formal and non-formal education. The development of Javanese language through formal education is carried out to children from elementary school (SD) in Kedungbanjar village, Sambeng.